Evaluation of Staged Under Frequency Load Shedding Strategy for Generator Trip Events at Arun Substation Using DIgSILENT Powerfactory - M. FITRA WALDI; MUHAMMAD DAUD; SELAMAT MELIALA; SALAHUDDIN SALAHUDDIN; TEUKU MULTAZAM (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Frequency stability is a key indicator of power system reliability, as disturbances such as generation loss can cause rapid frequency decline and potentially lead to a blackout. This study evaluates the effectiveness of a load shedding scheme using an Under Frequency Relay (UFR) at the Arun Substation through dynamic simulation in DIgSILENT PowerFactory. The scenario involves a sudden loss of generation, comparing conditions without and with UFR. Results show that without UFR, a 48.421 MW power loss causes the frequency to drop below 42 Hz in less than 16 seconds, leading to system failure. With a two-stage UFR scheme (27.6 MW at 49.5 Hz and 28.4 MW at 49.2 Hz), the frequency decline is arrested and the system stabilizes at 50.12 Hz within about 3 seconds. Thus, the UFR scheme is effective in maintaining system stability.